Lycopene and cognitive function. (29th May 2019) - Crowe-White, Kristi M.; Phillips, Tinsley A.; Ellis, Amy C.
Abstract: Decreases in cognitive function related to increases in oxidative stress and inflammation occur with ageing. Acknowledging the free radical-quenching activity and anti-inflammatory action of the carotenoid lycopene, the aim of the present review was to assess if there is evidence for a protective relationship between lycopene and maintained cognitive function or between lycopene and development or progression of dementia. A systematic literature search identified five cross-sectional and five longitudinal studies examining these outcomes in relation to circulating or dietary lycopene. Among four studies evaluating relationships between lycopene and maintained cognition, three reported significant positive relationships. Neither of the two studies reporting on relationship between lycopene and development of dementia reported significant results. Of four studies investigating circulating lycopene and pre-existing dementia, only one reported significant associations between lower circulating lycopene and higher rates of Alzheimer's disease mortality. Acknowledging heterogeneity among studies, there is insufficient evidence and a paucity of data to draw firm conclusions or tease apart direct effects of lycopene. Nevertheless, as low circulating lycopene is a predictor of all-cause mortality, further investigation into its relationship with cognitive longevity and dementia-related mortality is warranted.